Design And Modeling Of Dielectric Resonator Antenna Array Using New Feeding Method Over A Short Ended Microstrip - Qasaymeh, Yazeed M.A (2013)
Dielectric resonator antennas (DRAs) were developed for the use in the microwave and millimeter frequency band due to their attractive radiation characteristics. However, DRA are typically low gain antennas therefore DRA can be arrayed to achieve higher gain. Whereas, most of the DRA array techniques showed a limited success to reduce the array size and decrease the design complexity. This work focused on development and modeling of a dielectric resonator antenna (DRA) array from a novel arrangement of the dielectric resonators (DRs) to enhance the antenna gain and reducing array size. This simple arrangement also can be used to achieve wideband resonant and circular polarization in parallel with improved gain. The DRA array was excited by a microstrip line with few coupled slots positioned on the top of a metallic ground plane. To improve the gain, the slot positions were determined based on the characteristics of voltage allocation over a short ended microstrip feeder. Four array designs were developed in this work. This new feeding method can be employed to enhance the bandwidth or acquiring circular polarization. The Notched dielectric resonators were used to enhance the bandwidth while dielectric elements were rotated 45° with respect to the sides of the exciting slots to generate the circular polarization pattern. The DRA array structure was modeled into a parallel RLC resonant circuit using Agilent ADS software. Modeling is used to only calculate the dimensions of the DRs.